2016
DOI: 10.7439/ijbar.v7i6.3330
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level of school children of age 10-13 years

Abstract: Aim: To assess physical activity level of school children of age 10-13 years. Objectives: To assess and grade physical activity level in children of age 10-13 years using Physical Activity Questionnaire for Children (PAQ-C) classified into: Light Physical activity; Moderate Physical activity; Moderate to vigorous Physical activity and High Physical activity. Methodology: This is Questionnaire based survey study which was conducted on 100 school going children of 10-13 years who were present on the day of surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
4
5
0
Order By: Relevance
“…In line with the present study, several other studies 8,13,14,23,24 have also found less PA among girls compared to males. The probable reasons for this finding were due to the weakest participation of girls in organized sport.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with the present study, several other studies 8,13,14,23,24 have also found less PA among girls compared to males. The probable reasons for this finding were due to the weakest participation of girls in organized sport.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in consistent with previous studies. 8,13,23,24 A study done by Rashmi Ronghe et al 14 and Hemal Dave et al 13 used a PAQ-C to measure PA and rest of studies used a different methodology to find out a PA but showed a similar findings of decline in PA among school children. A longitudinal study done by Philip R. Nader 23 et al on 1032 participants from age 9to 14 years using accelerometer and found a significant decrease in PA over a time with boys found to be more active compared to girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scoring 1-1.9 was taken as LPA, 2-2.9 is MPA, 3-3.9 as MVPA, 4-4.9 as VPA and 5 as HPA. [9][10][11][12] Nutritional status was assessed through weight for age (underweight), height for age (stunting) and BMI for age (thinning) according to WHO criteria. 13 Each child's height and weight were measured in the metric system, using standardized technique.…”
Section: Methodsmentioning
confidence: 99%